Select Neuropeptides and their G-Protein Coupled Receptors in Caenorhabditis Elegans and Drosophila Melanogaster - Bendena, William; Campbell, Jason; Zara, Lian; Tobe, Stephen S.; Chin-Sang, Ian (Frontiers in Endocrinology, 2012)
The G-protein coupled receptor (GPCR) family is comprised of seven transmembrane domain proteins and play important roles in nerve transmission, locomotion, proliferation and development, sensory perception, metabolism, and neuromodulation. GPCR research has been targeted by drug developers as a consequence of the wide variety of critical physiological functions regulated by this protein family. Neuropeptide GPCRs are the least characterized of the GPCR family as genetic systems to characterize their functions have lagged behind GPCR gene discovery. Drosophila melanogaster and Caenorhabditis elegans are genetic model organisms that have proved useful in characterizing neuropeptide GPCRs. The strength of a genetic approach leads to an appreciation of the behavioural plasticity that can result from subtle alterations in GPCRs or regulatory proteins in the pathways that GPCRs control. Many of these invertebrate neuropeptides, GPCRs and signaling pathway components serve as models for mammalian counterparts as they have conserved sequences and function. This review provides an overview of the methods to match neuropeptides to their cognate receptor and a state of the art account of neuropeptide GPCRs that have been characterized in D. melanogaster and C. elegans and the behaviours that have been uncovered through genetic manipulation.